1978
DOI: 10.1080/0028825x.1978.10426874
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nonstructural carbohydrate reserves inChionochloa rigidaandC. macra,and their short-term response to fire

Abstract: The relationships of growth and flowering to storage of nonstructural carbohydrate reserves and the influence of the pastoral management practice of burning on these relationships have been investigated in Cizionoclzioa rigida and C. macra on the Old Man Range, Central Otago.Growth, as measured by elongation of the youngest exposed leaf, decreased significantly with increasing altitude. It was significantly greater in C. rigida than in C. macra. Leaf dieback did not show a significant species difference, but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…As well as flowering following warm summers, some Chionochloa species also flower heavily after being burned in wildfires (Payton and Brasch 1978;Payton and Mark 1979) despite having reduced carbohydrate levels at that time. Payton and Mark (1979) showed that in C. rigida, plants invariably flowered heavily in the year after fire, and it then took 14 yr of reduced growth and flowering for biomass levels to recover to prefire levels.…”
Section: Biology Of Chionochloa Pallensmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as flowering following warm summers, some Chionochloa species also flower heavily after being burned in wildfires (Payton and Brasch 1978;Payton and Mark 1979) despite having reduced carbohydrate levels at that time. Payton and Mark (1979) showed that in C. rigida, plants invariably flowered heavily in the year after fire, and it then took 14 yr of reduced growth and flowering for biomass levels to recover to prefire levels.…”
Section: Biology Of Chionochloa Pallensmentioning
confidence: 99%
“…This new tiller is not competent to flower for perhaps 3-5 yr depending on resource levels, but even in the heaviest flowering years only a small percentage of tillers (!20%) are consumed by flowering, so a shortage of competent tillers should not limit flowering. However, heavy flowering years do deplete the plant's stores of nonstructural carbohydrates (Payton and Brasch 1978).…”
Section: Biology Of Chionochloa Pallensmentioning
confidence: 99%
“…on New Zealand species with succe .. (e.a., Scott 1961Scott , 1977aMark 1969;Payton &. Brasch 1978).…”
mentioning
confidence: 99%
“…Methods used to collect and prepare samples for nutrient analyses are described in Payton & Brasch (1978). Plant material was stripped of all dead material and separated into leaf* and stem.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Payton & Brasch (1978) and Payton & Mark (1979) examined the short and longer term effects of spring burning on growth, flowering, and nonstructural carbohydrate reserves in snow tussocks. This paper integrates that work with an examination of the effects of fire on nutrient concentrations in Chionochloa rigida.…”
Section: Introductionmentioning
confidence: 99%